2012
DOI: 10.1111/ffe.12019
|View full text |Cite
|
Sign up to set email alerts
|

Unified characterisation of in‐plane and out‐of‐plane constraint based on crack‐tip equivalent plastic strain

Abstract: Constraint can be divided into two conditions of in‐plane and out‐of‐plane, and each of them has its own parameter to characterize. However, in most cases, there exists a compound change of both in‐plane and out‐of‐plane constraint in structures, a unified measure that can reflect both of them is needed. In this paper, the finite element method (FEM) was used to calculate the equivalent plastic strain (ɛp) distribution ahead of crack tips for specimens with different in‐plane and out‐of‐plane constraints, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 17 publications
(54 reference statements)
8
101
0
Order By: Relevance
“…[27][28][29][30] Mostafavi et al 27,28 have defined a new constraint parameter u which can quantify the both constraints. And then, a modified unified parameter A p was defined by Yang et al 29 Thus, in this article, different SENB specimens were selected, and the matching of crack-tip constraint between different specimens was systematically studied based on the unified constraint parameter A p .…”
Section: 11mentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30] Mostafavi et al 27,28 have defined a new constraint parameter u which can quantify the both constraints. And then, a modified unified parameter A p was defined by Yang et al 29 Thus, in this article, different SENB specimens were selected, and the matching of crack-tip constraint between different specimens was systematically studied based on the unified constraint parameter A p .…”
Section: 11mentioning
confidence: 99%
“…29 Thus, in this article, the areas surrounded by the e p = 0.2 isoline at the crack tip at different J-integrals were calculated.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…It has been identified that both the constraint parameter Q and stress triaxiality factor h are not a good unified representative of constraint, and a monotonic trend curve does not exist between the parameters (Q and h) and fracture toughness for various specimens with different in-plane and out-of-plane constraints under elastic-plastic fracture conditions [12,15,16,18,60]. The reason for this is that the two parameters are not equally sensitive to both in-plane and out-of-plane constraints.…”
Section: Correlations Of Ccg Rate With Creep Constraint Parameters R mentioning
confidence: 99%
“…They argued that there is no significant difference in the plastic zone sizes at fracture between in-plane and out-of-plane constraints, and the parameter u is equally sensitive to in-plane and out-of-plane constraints. However, finite element method (FEM) calculations by Yang et al [15,16] show that the constraint parameter u has its limitation in characterizing constraint at higher J-integral for the ductile material with higher fracture toughness due to the extension of the plastic zone size to the specimen boundaries. Thus, they defined a new unified constraint parameter A p by modifying the parameter u as follows [15,16]:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation